Treatment of Huge Hepatocellular Carcinoma Using Cinobufacini Injection in Transarterial Chemoembolization: A Retrospective Study - Dong, Jun (Evid Based Complement Alternat Med, 2016)
The aim of this study is to examine the safety and efficacy of Cinobufacini injection in transarterial chemoembolization (TACE) for treatment of huge hepatocellular carcinoma (HCC). Clinical data of 56 consecutive patients with HCC larger than 10 cm who had been treated with TACE between December 2010 and August 2014 were retrospectively analyzed. Among these patients, 31 belonged to the Cinobufacini group and 25 belonged to the epirubicin group. The clinical efficacy, survival time, and adverse events in patients in the two groups were compared. The objective response rate in the Cinobufacini group was significantly higher than that in the epirubicin group (53.6% versus 23.1%, P = 0.022). The median survival time (10.6 versus 14.1 months, χ (2) = 0.092, P = 0.762) and the median time to progression (4.9 versus 5.7 months, χ (2) = 0.097, P = 0.756) were similar between the groups. The incidence rate of adverse events was lower in the Cinobufacini group than in the epirubicin group (P < 0.05). The short-term clinical efficacy of Cinobufacini is better than that of epirubicin in TACE for treating huge HCC, while their long-term clinical efficacy is similar. However, lower incidence of adverse events was noted in TACE using Cinobufacini rather than epirubicin.